Monetary and Fiscal Policy in Times of Crises: A New Keynesian Perspective in Continuous Time - Bernd Hayo; Britta Niehof (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
To analyse the interdependence between monetary and fiscal policy during a financial crisis, we develop an open-economy DSGE model with monetary and fiscal policy as well as financial markets in a continuous-time framework based on stochastic differential equations. Monetary policy is modelled using both a standard and a modified Taylor rule and fiscal policy is modelled as either expansionary or austere. In addition, we differentiate between open economies and monetary union members. We find evidence that the modified Taylor rule notably reduces the likelihood that the financial market crisis affects the real economy. But if we assume that households are averse with respect to outstanding government debt, we find that a combination of expansionary monetary policy and austere fiscal policy provides better stabilisation of both domestic and foreign economies in terms of both output and inflation. In the case of a monetary union, we find that stabilisation of output in the country where the financial shock originates is no longer as easy and, in terms of prices, there is now deflation in the country where the crisis originated and a positive inflation rate in the other country.
Keywords: C63; E44; E47; E52; E62; F41; 330; New Keynesian Models; Financial Crisis; Dynamic Stochastic General Equilibrium Models; Continuous Time Model; Fiscal Policy; Monetary Policy